The sales agility code : deploy situational fluency to win more sales - Vazzana, Michelle; Doyle, Lisa Sottosanti (McGraw Hill-Ascent Audio, 2023)
The world of sales has become less predictable and more competitive in recent years. Buying decisions are more complex, differentiation between suppliers is difficult to discern, and high-quality information is readily available. The salespeople who excel are agile-choosing a path based on the buying situations they face and continually re-assessing those choices. In The Sales Agility Code, leaders at industry-leading sales training and development firm VantagePoint Performance help you learn and replicate what the highest-performing salespeople do to succeed in an unpredictable and ever-changing market. This groundbreaking guide teaches you how to shift to a buyer-focus perspective and assess customer situations from multiple perspectives; make sense of buyers' situations by considering and weighing all available data and your own insights; choose a sales approach that aligns with the customer situation with your prioritized sales objective; execute a variety of sales tactics that will move the sales opportunity forward; and make in-the-moment adjustments as the buyer's situation evolves. With The Sales Agility Code, you have everything you need to understand the buyer, the buying situation, and the buyer's needs so you can consciously choose the best approach for each stage in each deal-which will invariably result in more sales.